The Optimal Financing Decision of Indonesia Digital Network (IDN) - Arsiyanti, Ida; Wiryono, Sudarso Kaderi (The Indonesian Journal of Business Administration, 2014)
Abstract. Becoming a broadband wireless access operator is in line with the transformation of Telkom’s business to Telecommunication, Information, Media, and Edutainment (TIME). In order to deliver IME service, high speed bandwidth is required so there is no other choice but to prepare network with true broadband capability. Regarding that poin, Telkom plans to focus on the Indonesia Digital Network (IDN) until 2020 for development of internet broadband, pitching the initiative to Indonesian  as a way to bridge the digital divide suffered by the developing country and also significantly boost its GDP. IDN is a vision of true broadband infrastructure development of Telkom by end-to-end (user terminals, access, transport and service). IDN is a mega project that requires large amount of financing support. Missmanagement on financing strategy could affect Telkom’s long-run equity performance. The connections between capital structure and investment decisions should be most apparent when a company undertakes a large investment. By taking the right financings decision, IDN is expected to be able to be developed without cause any financial difficulty for Telkom. The objective of this final project is to formulate  financing strategy for IDN Project at the lowest cost of capital and the optimal mix of debt and equity that maximizes firm value itself. The financing decision for IDN Project despite to achieve the cheapest financing, should also encourage the overall company’s capital structure towards optimal, respectively. Keywords : cost of capital, company capital structure, firm value, financing source